2010
DOI: 10.1371/journal.pone.0009786
|View full text |Cite
|
Sign up to set email alerts
|

4E10-Resistant HIV-1 Isolated from Four Subjects with Rare Membrane-Proximal External Region Polymorphisms

Abstract: Human antibody 4E10 targets the highly conserved membrane-proximal external region (MPER) of the HIV-1 transmembrane glycoprotein, gp41, and has extraordinarily broad neutralizing activity. It is considered by many to be a prototype for vaccine development. In this study, we describe four subjects infected with viruses carrying rare MPER polymorphisms associated with resistance to 4E10 neutralization. In one case resistant virus carrying a W680G substitution was transmitted from mother to infant. We used site-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 61 publications
3
48
0
Order By: Relevance
“…Co-administration of 4E10 and 2F5 results in a synergistic neutralizing effect in vitro (Zwick et al, 2001b). To note, substitutions in the MPER contributed to the resistance to 4E10 (Gray et al, 2008;Nakamura et al, 2010). The safety and tolerability of 4E10 for clinical use have also been confirmed by a phase 2 clinical study (Joos et al, 2006).…”
Section: Passive Immunization Using Neutralizing Antibodiesmentioning
confidence: 87%
“…Co-administration of 4E10 and 2F5 results in a synergistic neutralizing effect in vitro (Zwick et al, 2001b). To note, substitutions in the MPER contributed to the resistance to 4E10 (Gray et al, 2008;Nakamura et al, 2010). The safety and tolerability of 4E10 for clinical use have also been confirmed by a phase 2 clinical study (Joos et al, 2006).…”
Section: Passive Immunization Using Neutralizing Antibodiesmentioning
confidence: 87%
“…The study demonstrated that W680G point mutation was necessary to confer 4E10 resistant phenotype (Nakamura et al, 2011). In another subject a W680R point mutation caused variable resistant to 4E10 (Nakamura et al, 2011). A fourth subject possessed a F673L point mutation also associated with 4E10 resistance (Nakamura et al, 2011).…”
Section: Point Mutations Associated With Evasion Of Antibody Mediatedmentioning
confidence: 92%
“…Mutagenesis studies have shown that the amino acid residues W672, F673 and W680 are indispensable for recognition by 4E10 (Zwick et al, 2005). Indeed, a recently published study describing four subjects infected with viruses carrying rare MPER polymorphisms associated with resistance to 4E10 neutralization has shown that three subjects had W680 polymorphism, including a W680G point mutation (Nakamura et al, 2011). The study demonstrated that W680G point mutation was necessary to confer 4E10 resistant phenotype (Nakamura et al, 2011).…”
Section: Point Mutations Associated With Evasion Of Antibody Mediatedmentioning
confidence: 96%
See 2 more Smart Citations